1991
DOI: 10.2337/diab.40.8.1041
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Islet Cytodifferentiation by Fetal Mesenchyme in Adult Pancreatic Ductal Epithelium

Abstract: Recombinant tissue consisting of adult ductal epithelium isolated from pancreas and fetal mesenchyme was transplanted subcutaneously in the inguinal region of nude mice or epididymal fat pads of rats with a tissue chamber device for short-term (8-day) or long-term (6- to 12-wk) duration. We found that recombinant tissue underwent morphogenesis and cytodifferentiation, thereby forming islets that contained cells immunocytochemically positive for insulin and glucagon. Islet cytodifferentiation occurred in approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 15 publications
(19 reference statements)
7
42
0
Order By: Relevance
“…The authors postulated that the newly formed beta cells derived from precursor cells in the duct epithelium. Another study [5] transplanted adult rat pancreatic duct epithelium under the skin of nude mice, and found only insulin-positive cells in the vicinity of ducts that were implanted with fetal mesenchyme. While the appearance of insulin-positive cells in duct cell preparations is interesting, persistent caution will be needed to distinguish newly formed from initially "contaminating" endocrine cells; it is also not known whether the presence of duct cells can affect the survival and function of neighboring islets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors postulated that the newly formed beta cells derived from precursor cells in the duct epithelium. Another study [5] transplanted adult rat pancreatic duct epithelium under the skin of nude mice, and found only insulin-positive cells in the vicinity of ducts that were implanted with fetal mesenchyme. While the appearance of insulin-positive cells in duct cell preparations is interesting, persistent caution will be needed to distinguish newly formed from initially "contaminating" endocrine cells; it is also not known whether the presence of duct cells can affect the survival and function of neighboring islets.…”
Section: Discussionmentioning
confidence: 99%
“…New beta cells might be formed by differentiation from stem cells or precursor cells [1,2,3,4], by transdifferentiation of other pancreatic cell types [5,6,7,8,9] or by replication of beta cells [10,11,12]. These processes could occur within or outside the islets of Langerhans.…”
mentioning
confidence: 99%
“…Since glucose transfers between fetuses and the maternal body through the placenta (Hay and Anderson, 2001), as shown in this experiment, B-cells damaged by STZ treatment do not increase the fetal plasma glucose concentration; thus, it is possible to maintain a constant condition without induction of hyperglycemia, which is beneficial for the elucidation of the B-cell neogenesis mechanism. There have been studies of the epithelial-mesenchymal interaction in the organogenesis of the pancreas (Wessels and Cohen, 1967;Pictet and Rutter, 1972;Dudek et al, 1991;Gittes et al, 1996) and Miralles et al (1998) demonstrated that the presence of the mesenchyme leads the primordial pancreas to the exocrine part and that this effect is produced by follistatin secreted from the mesenchyme. Of the cells that constitute the primordial pancreas, precursor cells with no sensitivity to follistatin are assumed to differentiate into endocrine cells, and growth factors derived from the mesenchyme or exocrine cells are considered to promote sustained expression of PDX-1.…”
Section: Discussionmentioning
confidence: 99%
“…During embryogenesis, stem cells within the pancreatic duct epithelium give rise to both the endocrine and acinar cells of the pancreas [51]. Adult pancreatic duct cells retain the capacity for expansion and differentiation suggesting that adult pancreatic ducts may still harbor stem cells capable of differentiating into ß-cells in vivo [52][53][54]. This notion is supported by the ability of ductal tissue in vitro to be harvested, expanded, and cultured to form islet-like structures capable of glucose responsive insulin secretion [54].…”
Section: Pancreatic Stem Cellsmentioning
confidence: 99%